Health needs of the rural area of Quezon City and their educational implications - Lara, Alma F. 1925- (1954)
This study and investigation provide the answers to the following questions: (1) What are the major health problems of the rural area of Quezon City the solution of which would be approachable largely through education? (2) To what extent and in what manner has the school assisted in attempting to solve these health problems? (3) Does an efficient method of coordination of the health activities of the schools, Quezon City Health Department and other organizations concerned with health exist and in what manner is done? (4) How may the school serve further to help meet the health needs of the community?
Typewritten.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Hygiene, Rural -- Philippines -- Quezon City